PREDICTION OF SUBSURFACE FRACTURE IN MINING ZONE OF PAPUA USING PASSIVE SEISMIC TOMOGRAPHY BASED ON FRESNEL ZONE - HERLAN SETIADI (NIM : 10207070); Pembimbing : Dr. Eng. Bagus Endar Bachtiar N,
Prediction of fracture in a block cave underground mine is very important to monitor the structure of the fracture can be harmful to the mining activities. Many methods can be used to obtain such information, such as TDR (Time Domain Reflectometry) and open hole. Both of them have limitations in range measurements. Passive seismic tomography is one of the subsurface imaging methods. It has advantages in terms of measurement range, cost, and rich of rock physical information. This passive seismic tomography studies using Fresnel zone to model the wavepath by using frequency parameter. Fresnel zones was developed by Nurhandoko in 2000. The result of this study is tomographic P and S wave velocity to predict the position of fracture. The study also attempted to use the sum of the wavefronts to obtain the position and time of seismic events occurence. Fresnel zone tomography and the summation wavefront can predict the locations of the geological structure of the mining area as well.